Systematized biosynthesis and catabolism regulate citrulline accumulation in watermelon. (June 2019) - Joshi, Vijay; Joshi, Madhumita; Silwal, Diwas; Noonan, Kayce; Rodriguez, Sierra; Penalosa, Arianne
Abstract: Citrulline, a non-protein amino acid, is present in large amounts in watermelon ( Citrullus lanatus (Thunb.) Matsum. & Nakai Cucurbitaceae) fruits. Amino acid profiling of various tissues of cv. Charleston Gray during plant development confirmed progressive accumulation of citrulline only in the fruit flesh and rind tissues. Citrulline content was positively correlated with precursor (ornithine) and by-product (arginine) amino acids during fruit ripening. Genetic variation in the partitioning of citrulline and related amino acids in the flesh and rind tissues was confirmed in a sub-set of watermelon cultivars. No correlation was established between morphological fruit traits (size and rind properties) and citrulline content. To understand the regulation of citrulline accumulation, we investigated the expression of genes associated with its biosynthesis and catabolism in flesh and rind tissues during fruit development. The expression of ornithine carbamoyltransferase ( OTC ) involved in the ultimate step of citrulline synthesis remained steady in both tissues. The expression of N -acetylornithine aminotransferase ( N-AOA ) involved in the production of N -acetylornithine and N -acetylornithine deacetylase ( AOD-3 ) involved in ornithine synthesis coincided with increasing accumulation of citrulline in flesh and rind tissues during fruit development. Down-regulation N -acetylornithine-glutamate acetyltransferase ( N-AOGA ) suggests the subordinate role of the non-cyclic pathway in citrulline synthesis. Eccentricity between citrulline accumulation and expression of carbamoyl phosphate synthases ( CPS-1, CPS-2 ) during fruit development suggest that the localized synthesis of carbamoyl phosphates may not be required for citrulline synthesis. Most genes involved in citrulline break-down (Argininosuccinate synthases - ASS-1, ASS-2, and ASS-3, Argininosuccinate lyases - ASL-1, Ornithine decarboxylase - ODC, Arginine decarboxylase - ADC ) were consistently down-regulated during fruit development. Graphical abstract: A steady accumulation of citrulline in developing watermelon fruit is regulated by orchestrated induction of genes involved in biosynthesis along with down-regulation of citrulline degradation.Image 1 Highlights: A steady increase in citrulline accumulation in the flesh and rind of developing watermelon fruit. A positive correlation between citrulline, its precursor (ornithine) and by-product (arginine). Expression of genes involved in the biosynthesis coincided with citrulline accumulation. Down-regulation of genes involved in citrulline catabolism during fruit development.